Autopercepción del anti reflejo azul en usuarios de lentes oftálmicos frente a síntomas de fatiga ocular (2021)
In the visual system, the spectrum of blue light can generate certain effects due to prolonged exposure in relation to electronic emitting devices such as: computers, tablets and cell phones that have represented an important source of exposure to blue light, thus associating the use of anti-reflection in ophthalmic lenses for the attenuation of the impact of blue light on the ocular surface and the symptoms reported in patients